Inventions of the heart - Connealy, Mary (Connealy, Mary. Lumber baron's daughters, 2022)
"After her sister's marriage, Michelle Stiles is left hiding at Two Harts Ranch with the handsome but stubborn Zane Hart. She's managed to stay one step ahead of her stepfather and his devious plans, but if he finds her, she will no longer be safe. Zane has problems of his own. Having discovered a gold mine on his property, he must figure out how to harvest it without kicking off a gold rush. Michelle, educated and trained to run her father's business, wants to manage all aspects of the mine, but Zane thinks for a person so smart she can have some misguided ideas. Running the mining operation will be a dangerous job, and he can't risk putting her in harm's way. But danger finds Michelle anyway when she's suddenly attacked. If they go to the sheriff, they'll reveal her location, but if they do nothing ... their troubles have only just begun"--Page 4 of cover.